1987
DOI: 10.1128/aem.53.12.2821-2826.1987
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of the deepoxy trichothecenes: deepoxy HT-2, deepoxy T-2 triol, deepoxy T-2 tetraol, deepoxy 15-monoacetoxyscirpenol, and deepoxy scirpentriol

Abstract: The production of deepoxy metabolites of the trichothecene mycotoxins T-2 toxin and diacetoxyscirpenol, including deepoxy HT-2 (DE HT-2), deepoxy T-2 triol, deepoxy T-2 tetraol, deepoxy 15-monoacetoxyscirpenol, and deepoxy scirpentriol is described. The metabolites were prepared by in vitro fermentation with bovine rumen microorganisms under anaerobic conditions and purified by normal and reverse-phase high-pressure liquid chromatography. Capillary gas chromatographic retention times and mass spectra of the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 31 publications
(31 reference statements)
1
24
0
1
Order By: Relevance
“…As representative example Table 3 shows the results for norNIV C. These findings are in agreement with the fact that the epoxy-group plays an important role in the toxicity of trichothecenes [14,15] using the 5-bromo-29-deoxyuridine incorporation assay accessing DNA synthesis showed that the de-epoxides of DON and NIV were 24 and 51 times less toxic compared to the toxins with an intact epoxide ring [15]. It was also shown in the brine shrimp bioassay that the de-epoxides are much less acutely toxic than the corresponding trichothecenes [16]. Furthermore, in the case of the T2 trichothecene i.p.…”
Section: Resultssupporting
confidence: 86%
“…As representative example Table 3 shows the results for norNIV C. These findings are in agreement with the fact that the epoxy-group plays an important role in the toxicity of trichothecenes [14,15] using the 5-bromo-29-deoxyuridine incorporation assay accessing DNA synthesis showed that the de-epoxides of DON and NIV were 24 and 51 times less toxic compared to the toxins with an intact epoxide ring [15]. It was also shown in the brine shrimp bioassay that the de-epoxides are much less acutely toxic than the corresponding trichothecenes [16]. Furthermore, in the case of the T2 trichothecene i.p.…”
Section: Resultssupporting
confidence: 86%
“…Deepoxy-DON is obtained after de-epoxidation of DON; several bacterial species and enzymes are able to catalyze this reaction 19 . The lower toxicity of deepoxy-DON, as compared to DON has been demonstrated in vitro on Swiss mouse 3T3 fibroblasts 16 , lymphocytes 17 and brine shrimp 25 . In vivo supplementation of DON-contaminated feed, with bacteria and/or an enzyme able to de-epoxidize DON, induced a reduction of the toxicity as shown by measurement of zootechnical or immune parameters 18 26 27 .…”
Section: Discussionmentioning
confidence: 96%
“…Few studies on the in vitro biotransformation of DAS in farm animals have been identified. DAS was incubated for 12, 24 and 48 h under anaerobic conditions in rumen fluids (Swanson et al., ). MAS, SCT and their deepoxide metabolites were detected in the incubates.…”
Section: Assessmentmentioning
confidence: 99%